EFFECT OF ECP ON THE STIMULATION OF LEUCOCYTE NUMBER AND PHAGOCYTOSIS OF JAPANESE EEL Anguilla japonica AGAINST Edwardseilla tarda NUF251 - Hari Suprapto (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2000)
The extra cellular product (ECP) was rapidly induced leucocyte number compared to Edwardseilla tarda NUF251 in eel blood. The reason could be live cells need time to multiplied in eel body whereas the ECP composed of high protein therefore induce the leucocyte production in short time. The number of leucocyte in eel blood were not different between inactivated ECP and control eels. Although the leucocyte number increased gradually in live cells injected eel but have not correlation to increasing phagocytosis index (PI) in vivo phagocytosis. The PI and phagocytic rate (PR) of in vivo phagocytosis relatively constant from 24-96 h post injection.